Endodontic practice - Grossman, Louis Irwin (Philadelphia, Pa. : Lea & Febiger, 1978)
Endodontic Practice by Louis Irwin Grossman is a foundational text in the field of endodontics, widely regarded for its clear, systematic approach to the diagnosis, treatment, and prevention of diseases of the dental pulp and periradicular tissues. Now in its 9th edition, this comprehensive volume provides detailed guidance on clinical techniques, instrumentation, and materials used in root canal therapy, supported by numerous illustrations. Designed for dental students, educators, and practicing clinicians, the book bridges fundamental biological principles with practical application, emphasizing evidence-based procedures and clinical decision-making. Grossman’s work has contributed significantly to shaping modern endodontic standards and remains a trusted resource in dental education and practice.
Prvé až štvrté vydanie publikované pod titulom: Root canal therapy
Obsahuje bibliografie a register
Keywords: endodoncia; lekárstvo zubné; starostlivosť stomatologická; vybavenie stomatologické; spôsoby vykonávania stomatologickej praxe, doporučené; monografia